Water sorption and solubility of glass ionomer cements indicated for atraumatic restorative treatment considering the time and the pH of the storage solution - Renally Bezerra Wanderley e LIMA; Julyanna Filgueiras Gonçalves de FARIAS; Ana Karina Maciel ANDRADE; Fábia Danielle Sales da Cunha Medeiros e SILVA; Rosângela Marques DUARTE (Faculdade São Leopoldo Mandic, 2018)
Objective: Evaluate the water sorption and the solubility of glass ionomer cements considering the time and the pH of the storage solution. Methods: The materials used in this survey study were the following ones: Ketac Molar Easymix, Maxxion R, Vitro Molar, Vitremer and Vitro Fil LC. Fifteen specimens of each material were fabricated and subdivided into the storage solutions (deionized water, acid artificial saliva and neutral artificial saliva), having the mass measured in 24 hours, 7, 14 and 21 days. Water sorption and solubility values (µg/mm3) were obtained and submitted to the analysis of variance (ANOVA) and the Tukey test (p <0.05). Results: The water sorption values were statistically different for all the studied materials and solutions in each storage period, except for the Maxxion R. Considering the solubility, all the glass ionomer cements presented values that were not statistically different when evaluating the storage solutions, except for the Vitro Fill LC. Conclusion: The water sorption and the solubility of the studied glass ionomer cements were not influenced by the various storage solutions.